M.S. Myroshnychenko, Yu.М. Mishyn, М.М. Mishyna, І.А. Маrchеnkо, А.М. Burov - M.S. Myroshnychenko; Yu.М. Mishyn; М.М. Mishyna; І.А. Маrchеnkо; А.М. Burov (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Kidney diseases occupy one of the leading places in the overall structure of morbidity and are a socially significant problem due to the increase in pediatric patients. An important role in homeostasis and progression of kidney diseases is played by cytokines, which perform a number of biological functions and interact with other cells and tissues of the body.